Variation on a theme: Mycenaean early civilisation in a comparative perspective - Bajema, Marcus (Journal of Greek Archaeology, 2017)
To determine the usefulness of comparative studies to understand Mycenaean palatial society, it is first necessary to discuss early civilisations as a comparative category. In this regard it is important to note that the level of generalisation concerns a specific set of societies with similar emergent properties, which are subject to two complementary forms of evaluation. Firstly, models of early civilisations need to correspond to the archaeological and historical records of single cases, and, secondly, there needs to be a cross-cultural coherence to the models used. The interpretive strength of a comparative category depends on its success in this balancing act. Comparative studies are of limited use for evaluating the correspondence between models and data for specific societies. At most the differences in available sources between distinct cases might reveal biases, being the result of a reliance on a limited set of sources. The use of analogy to make inferences for a case based on another case is not comparative, and is not used here. The significant use of comparative categories lies in the coherence they bring to model building, as well as the stimulus provided by interpretive debates on particular aspects of early civilisations.